The effects of multidisciplinary education for nurses and physicians on the management of patients with multiple trauma - Farhad Heydari; Shahla Mohamadirizi; Mohammad Nasr-Esfahani (Kashan University of Medical Sciences, 2019)
Background: Trauma is a leading cause of death and disability in developing countries. In-service training is a strategy for improving health-care providers' trauma-related knowledge and skills. Objectives: The purpose of this study was to evaluate the effects of multidisciplinary education for nurses and physicians on the management of patients with multiple trauma. Methods: This quasi-experimental study was conducted in 2017-2018 in Al Zahra hospital, Isfahan, Iran. Initially, the triage-related characteristics of 200 patients with multiple trauma were documented using specific checklist. Then, a multidisciplinary education program on the Emergency Service Index (ESI) triage and advanced trauma life support (ATLS)-based trauma management was implemented for emergency department (ED) staff, including 80 emergency nurses and 82 medical residents. After the intervention, the triage-related characteristics of another sample of 200 patients with multiple trauma were documented similarly. Data analyses were conducted using the Chi-square, Mann-Whitney and Wilcoxon tests. Results: The mean of waiting time for the first visit by emergency medicine specialists, the relative frequency of endotracheal intubation, and the length of stay in the ED significantly decreased from 19.45 ± 13.41 min, 12%, and 7.55 ± 1.59 h at pretest to, respectively, 14.01 ± 1.81 min, 3%, and 3.91 ± 0.71 h at posttest. Moreover, the relative frequency of patients who were transferred directly from the ED to the operating room significantly increased from 13% at pretest to 27% at posttest. Conclusion: Multidisciplinary education based on the ESI triage and ATLS can reduce the waiting time for specialized care services, facilitate patient transfer from the ED to the operating room, and shorten patient stay in the ED. It is also partially effective in alleviating overcrowding in the ED.